A comparison of the legal frameworks supporting water management in Europe and China - Yang, X (Water science and technology : a journal of the International Association on Water Pollution Research, 2010)
This paper has compared the legal frameworks supporting water management in Europe and China, with special focus on integrated river basin management (IRBM) to identify synergies and opportunities in policymaking and implementation. The research shows that China has committed to the efficient management of water resources through various policy tools during the current period. This commitment, however, has often been interrupted and distorted by politics, resulting in the neglect of socioeconomic and environmental priorities. The European legal framework supporting water management underwent a complex and lengthy development, but with the adoption of the Water Framework Directive provides a policy model on which to develop an integrated and sustainable approach to river basin management, elements of which may help to meet the demands of the emerging 21st century Chinese society on these critical natural resources